Scientific approaches to the evaluation of the competitiveness of regions - Caurkubule, Z.; Kenzhin, Zh.; Sultanova, Z. (BUKETOV BUSINESS REVIEW, 2018)
In this article, the authors analyze various scientific approaches to assessing the competitiveness of regions. The assessment methods used by domestic and foreign economists are presented and critically evaluated. It is justified that in connection with a different understanding of competitiveness, the scientific polemic about methods is carried on. The authors come to the conclusion that a comprehensive assessment of the region’s competitiveness should include parameters characterizing the quality of life of the population, since the aim of any regional policy is to increase the well-being of citizens. In economic science, there are many methods for assessing the competitiveness of the region, based on various socio-economic concepts. The study allowed formulating the most complete definition of competitiveness. According to the authors, this term reflects the effective use of the resource base, the potential opportunities and prospects for full-fledged participation of the region in competition and access to interregional and global markets. The article presents a comparative analysis of all the methods examined and their current position in assessing regional competitiveness.